Depression among Tuberculosis Patients and its Association with Medication Adherence of Anti-Tuberculosis Drugs Literature Review - Rahma Bianita Pratiwi (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Tuberculosis or known as TBC is one of communicable disease that caused by the bacillus Mycobacterium tuberculosis. This disease is the major of public health problem due to it can spread easily from the patients to the healthy people by air transmission. In order to stop the transmission and improve the health status of the community, treatment is needed for patients with tuberculosis. But, almost people with tuberculosis patients had poor treatment and the factor that contribute to their adherence is depression. Depression and tuberculosis are frequently coexisting in individuals. Depression lead them having negative perception about the treatment and get misconceptions about TB disease. Therefore, most of tuberculosis patients with depression are having lower level of medication adherence. Objective: The purpose of this literature review is to analyze the association between depression among tuberculosis patients with medication adherence of anti-tuberculosis. Method:.This study uses the literature review method to review the results of research that has been published by previous researchers. The literature sources obtained were the results of searches from three online databases, namely Google scholars, Pubmed, and Scopus. which published in the range of 2018-2024. Result: Depression was significantly associated with medication adherence among people who had tuberculosis Conclusion: Depression appears to be a strong risk factor for treatment failure and default in these people with newly diagnosed tuberculosis and is associated with poor treatment outcome despite successful tuberculosis treatment. This could be happened because of long period time that needed to consume the treatment and complexity of the drug regimen.